Reseña de Barcelona, A. (Ed.) (2000), Metaphor and Metonymy at the Crossroads. A cognitive perspective, New York, Mouton de Gruyter. - González Macías, Miguel Ángel (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–> Se trata de reseña de Barcelona, A. (Ed.) (2000), Metaphor and Metonymy at the Crossroads. A cognitive perspective, New York, Mouton de Gruyter.